Rare bilateral vascular variations of the upper limb: a cadaveric case study - Ricky Smith; Yasith Mathangasinghe; David Gonsalvez (Journal of Cardiothoracic Surgery)
Abstract Arterial variations in the upper limb are of significant clinical importance, especially in procedures such as venepunctures, coronary artery bypass grafts, trauma reconstructive surgeries, brachial plexus nerve blocks, and breast reconstructions. This report presents previously undocumented arterial variations in the upper limbs in a 95-year-old female cadaveric donor. We observed bilateral superficial ulnar arteries originating at the cubital fossa, deviating from the previously reported origin at the proximal brachial artery. We found additional variations in the branches of the axillary artery: on the right side, two superior thoracic arteries emerged from the first part of the axillary artery, an accessory branch supplied the subscapular muscle, and the large subscapular artery arising from the third part of the axillary artery gave rise to both the lateral thoracic and posterior circumflex humeral arteries. On the left side, a common trunk was identified, giving rise to the transverse cervical, dorsal scapular, and accessory lateral thoracic and subscapular arteries. Moreover, the acromial artery originated directly from the axillary artery on both sides. This case report discusses the clinical significance of these unique vascular anatomical variants, their prevalence, and potential impact, emphasizing the importance for clinicians to be aware of such variations to enhance surgical planning and patient safety.